Analisis Kualitas Pelayanan dan Kepercayaan Terhadap Loyalitas Konsumen pada Perusahaan CV. Indah Laundry Palembang - Firmansyah Firmansyah; Henny Oktaviyani (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of service quality and trust both partially and simultaneously on customer loyalty at CV. Indah Laundry Palembang. The research method with Multiple Linear Regression Analysis is used to determine the effect of Service Quality (X1), Trust (X2), on loyalty (Y). The results of the t test show that the calculated t value for the service quality variable and the calculated t value for the variable is smaller than the sensitivity level value (Sig.) <0.05, meaning that the model is significant. The F test shows that the calculated f value is smaller than the sensitivity level value (Sig.) <0.05. The two variables, namely the service quality variable and the trust variable, the sensitivity level value (Sig.) <0.05, means that the model is significant. In conclusion, service quality and trust have an influence both partially and simultaneously on consumer loyalty at CV. Indah Laundry Palembang. Keywords: Service Quality, Trust, Loyalty